2017
DOI: 10.1073/pnas.1704227114
|View full text |Cite
|
Sign up to set email alerts
|

Distinct PKC-mediated posttranscriptional events set cytokine production kinetics in CD8+T cells

Abstract: Effective T cell responses against invading pathogens require the concerted production of three key cytokines: TNF-α, IFN-γ, and IL-2. The cytokines functionally synergize, but their production kinetics widely differ. How the differential timing of expression is regulated remains, however, poorly understood. We compared the relative contribution of transcription, mRNA stability, and translation efficiency on cytokine production in murine effector and memory CD8 + T cells. We show that the immediate and ample p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
127
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 60 publications
(136 citation statements)
references
References 43 publications
9
127
0
Order By: Relevance
“…We highlight that although the antigen threshold for producing different cytokines may be comparable, or indeed identical, there are multiple mechanisms that enable differential regulation. For example, it is clear that there are differences in bulk cytokine production kinetics (32,33), which may be a result of different mRNA expression and stability (35)(36)(37) and sequential production programs (32). Although differences in individual cytokine levels are clearly observed in individual experiments (see representative curves in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We highlight that although the antigen threshold for producing different cytokines may be comparable, or indeed identical, there are multiple mechanisms that enable differential regulation. For example, it is clear that there are differences in bulk cytokine production kinetics (32,33), which may be a result of different mRNA expression and stability (35)(36)(37) and sequential production programs (32). Although differences in individual cytokine levels are clearly observed in individual experiments (see representative curves in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A technically more demanding assay based on single-cell cytokine secretion has shown that a single pMHC can induce both TNFα and IL-2 implying that their antigen threshold is comparable (31). In addition, it is now clear that different cytokines exhibit different production kinetics (32,33) and production depends on continuous TCR/pMHC engagement (34). Therefore, the pMHC degradation rate may introduce apparent differences in thresholds with cytokines having faster production kinetics appearing to have a lower threshold.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the production of IFN-γ, TNF-α and IL-2 in primary CD8 + T cells is subject to the type of signal and the signal strength that T cells receive (Nicolet et al, 2017;Salerno et al, 2016Salerno et al, , 2017. These signals define not only transcriptional regulation but also posttranscriptional events and alter the stability and translation efficiency of cytokine mRNA, which can result in discrepancies in mRNA and protein levels for these cytokines (Salerno et al, 2017(Salerno et al, , 2019b(Salerno et al, , 2019a. Untranslated regions (UTRs) are key regulatory elements in this process, as they are required for the modulation of mRNA transcript stability, translation initiation, and translation efficiency (Mayr, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas murine T cells show a t1/2 >2h upon antigen stimulation [30], [33], human control T cells activated with -CD3/-CD28 only reach a t1/2 ~ 70min. This also translates into lower overall IFN- protein output in human T cells, both in terms of responding T cells (60-80% in murine wild type T cells versus 30-50% in human T cells upon PMA-Ionomycin stimulation [47], [54]), and in terms of production kinetics. In fact, even though human and murine T cells initiate the IFN- production in the same time frame, human T cells cease to produce IFN- faster.…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether ARE-deletion also modulated the IFN- protein production and/or kinetics, we activated ARE-Del and control T cells with -CD3/-CD28. To visualize the production kinetics, we added Brefeldin A for a maximum of the final 2h of stimulation [54], and measured the production of IFN- protein via intracellular cytokine staining. In nonactivated T cells, we did not observe any protein production by any T cell type (Figure 2C), indicating that like control T cells, ARE-Del T cells require T cell activation for cytokine production.…”
Section: Are-deletion Stabilizes Ifng Mrna and Augments Protein Produmentioning
confidence: 99%